Influence of immersion solution and dentin interaction on the solubility of ready-to-use or powder-liquid bioceramic endodontic sealers (Research, Society and Development, 2023)
The aim of this study was to evaluate the effect of immersion solution and interaction with dentin on the solubility of ready-to-use bioceramic NeoSEALER® Flo (NSF) or powder-liquid BioRoot RCS (BR). Molds with an internal diameter of 5 mm and a length of 1.5 mm were made of polyethylene or bovine dentin. After filling with NSF or BR, they were kept in an oven for 24 hours. After determining the initial mass on a precision scale, the specimens were immersed in 7.5 mL of distilled water (DW) or phosphate buffered saline solution (PBS) (n=8) for 7 or 14 days. The final mass was obtained after weighing until mass stabilization occurred. Solubility was evaluated according to the difference between the initial and final mass in percentage. Two-way ANOVA, Bonferroni and unpaired t-tests were used (α=0.05). After 7 days, both materials showed lower solubility in PBS than DW (p0.05), except for polyethylene/NSF in DW after 7 days (p